Perioperative, functional, and oncologic outcomes of laparoscopic partial nephrectomy versus open partial nephrectomy for complex renal tumors: a systematic review and meta-analysis - Zhang, Fan; Hu, Jiang-sheng; Zhang, Kai-yu; Liu, Xiao-hua (Frontiers in Oncology, 2024)
The primary aim of this present study is to undertake a comprehensive comparative analysis of the perioperative, functional, and oncologic outcomes associated with laparoscopic partial nephrectomy (LPN) and open partial nephrectomy (OPN) as interventions for the treatment of complex renal tumors, defined as PADUA or RENAL score ≥ 7.We systematically carried out an extensive search across four electronic databases, namely PubMed, the Cochrane Library, Embase, and Web of Science. Our objective was to identify pertinent studies published in the English language up to December 2023, and encompassed controlled trials comparing LPN and OPN as 2 interventions for complex renal tumors.This study encompassed a total of seven six comparative trials, involving 934 patients. LPN exhibited a noteworthy reduction in the length of hospital stay (weighted mean difference [WMD] -2.21 06 days, 95% confidence interval [CI] -2.8862, -1.5550; p < 0.00001), blood loss (WMD -2834.99 05mL, 95% CI -5155.5361, -612.4548; p = 0.01002), and overall complications (OR 0.3038, 95% CI 0.1419, 0.6279; p = 0.0091).However, noteworthy distinctions did not arise between LPN and OPN concerning parameters such as warm ischemia time, renal function, and oncological outcomes.This study reveals that LPN presents several advantages over OPN.These benefits encompass a shortened hospital stay, diminished blood loss, and a reduced incidence of complications. Importantly, LPN achieves these benefits while concurrently upholding comparable renal function and oncological outcomes.